Asparagine Synthetase Deficiency with Intracranial Hemorrhage Can Mimic Molybdenum Cofactor Deficiency - Abdel-Salam, Ghada M. H.; Abdel-Hamid, Mohamed S. (Neuropediatrics, 2020)
Here we report a consanguineous Egyptian family with two siblings presented with congenital microcephaly, early-onset epileptic encephalopathy, feeding difficulties, and early lethality. The condition was initially diagnosed as molybdenum cofactor deficiency as the brain imaging for one of them showed brain edema and intracranial hemorrhage in addition to the hypoplastic corpus callosum, vermis hypoplasia, and small-sized pons. Subsequently, whole exome sequencing identified a novel homozygous missense variant in exon 4 of ASNS gene c.397_398GT > CA (p.Val133Gln) confirming the diagnosis of asparagine synthetase deficiency syndrome. No discernible alternative cause for the intracranial hemorrhage was found. Our patient is the second to show asparagine synthetase deficiency and intracranial hemorrhage, thus confirming the involvement of ASNS gene. As such, it is important to consider asparagine synthetase deficiency syndrome in patients with microcephaly, brain edema, and neonatal intracranial hemorrhage.
Keywords: asparagine synthetase deficiency; microcephaly; epileptic encephalopathy; ASNS gene; intracranial hemorrhage